Aspirations and environmental performance feedback: a behavioral perspective for green supply chain management. Issue 6 (2nd September 2020) - Shou, Yongyi; Shan, Shuo; Chen, Anlan; Cheng, Yang; Boer, Harry
Abstract : Purpose: This study investigates the relationships between environmental performance feedback and green supply chain management (GSCM). It explores how environmental performance above or below aspirations affects the implementation of GSCM practices (specifically sustainable production [SP] and sustainable sourcing [SS]) through the lens of the behavioral theory of the firm (BTOF), which has received scant attention in the operations management literature. Design/methodology/approach: The study used data from the sixth round of the International Manufacturing Strategy Survey (IMSS). It employed hierarchical linear regression to test the proposed hypotheses. Moreover, the study tested an alternate model to rule out the possible role of financial performance aspirations in explaining the implementation of SP and SS. Findings: The results indicate that organizations determine their efforts put into the two GSCM practices according to environmental performance feedback: the greater the aspiration–environmental performance discrepancy, the stronger the efforts put into implementing GSCM practices. Originality/value: This study contributes to the GSCM literature by revealing the impact of environmental performance aspirations on the implementation of GSCM practices through the lens of the BTOF. It also extends the BTOF by applying it in the GSCM context and indicating that performance feedback is based on environmental performance instead of financial performance in this specific context.